Penyuluhan Pengelolaan Stress pada Lansia di Rumah Lansia Bahagia Bintan - Handayani, Wulan; Agustina, Puti; Lisandari, Yani; Kurniawan, Rizki (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Stress is an unavoidable reality of everyday life, caused by changes that require adjustment. After being given counseling, it is hoped that the elderly can understand stress management. After getting an explanation about stress management, participants Counselors are expected to know the meaning of stress, the signs and symptoms of stress, the causes of stress, and stress management. The problem is that some elderly people in Bintan Happy House experience mild stress because they still do not understand how to manage stress in the elderly. The basic thing that is offered to help solve the problem is counseling activities for the elderly at Bintan Happy House, which are packaged with the activity name "Health Education on Stress Management in the Elderly at Bintan Happy House". Activities are carried out using lecture, discussion, and question-and-answer methods. The results obtained after education were that the elderly who took part in health education activities about stress management in the elderly could understand how to manage stress in the elderly at Bahgia Bintan House. Thus, from the evaluation that has been carried out, the elderly in Bintan Happy House can manage stress well.